Determinasi Kualitas Penyajian Laporan Keuangan Baitul Maal Wa Tamwil - Dwi Arini Nursansiwi; Agus Khazin Fauzi; Baiq Minatul Inayah; Armiani Armiani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
Presentation of quality financial reports is an important component for an organization or institution so that it must be guided by applicable financial accounting standards. On this basis, this study aims to empirically examine the effect of the variables on understanding sharia accounting standards, sharia supervisory boards, Islamic corporate governance on the quality of financial statement presentation at BMT Mataram city. The data collection technique used a questionnaire distributed to BMT managers, with a total population of 28 BMT and saturated sampling was used as a sampling technique. Data analysis using multiple linear regression. The findings found that understanding of Islamic accounting standards has no effect on the quality of presentation of financial statements with a value of thitung < ttabel (1,418 < 1,997) and the sharia supervisory board has no effect on the quality of presentation of financial statements which can be seen from the value of thitung < ttabel (1,493 < 1,997). Meanwhile, Islamic corporate governance has an effect on the quality of presentation of financial statements with mark thitung > ttabel (3,311 > 1,997)